2017
DOI: 10.22605/rrh4045
|View full text |Cite
|
Sign up to set email alerts
|

Remote eye care screening for rural veterans with Technology-based Eye Care Services: a quality improvement project

Abstract: Remote eye care screening for rural veterans with Technology-based Eye Care Services: a quality improvement project

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Although overall complication rates were low (1.17 percent), the complication rates in high‐risk eyes were over three times higher. Other significant risk factors, similar to those noted previously in the literature, 10‐12,16,18 included complex cataract surgery, black race, and rurality 40 . Although the presence of preoperative ocular conditions was positively associated with higher complication rates (though this association was not statistically significant), once risk category was added to the model, there was a lower risk of complications among patients with 1‐2 preoperative ocular conditions compared to those with none.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although overall complication rates were low (1.17 percent), the complication rates in high‐risk eyes were over three times higher. Other significant risk factors, similar to those noted previously in the literature, 10‐12,16,18 included complex cataract surgery, black race, and rurality 40 . Although the presence of preoperative ocular conditions was positively associated with higher complication rates (though this association was not statistically significant), once risk category was added to the model, there was a lower risk of complications among patients with 1‐2 preoperative ocular conditions compared to those with none.…”
Section: Discussionsupporting
confidence: 63%
“…Even in the early Choice period (FY15), we found that almost 30 percent of all Veterans received cataract surgery in CC, consistent with other recent findings on the overall care provided to Veterans through CC 4,38 . These findings may reflect increased demand for ophthalmology services due to the aging Veteran population as noted earlier, the growing prevalence of diagnosed eye conditions relative to the resources currently available in VA, and/or a desire to have the procedure done close to the Veteran's home (particularly among rural Veterans) 39,40 . If these trends continue, it will be important to better understand why Veterans use CC for cataract surgeries, identify patient populations best suited for surgery through CC vs VA to minimize risk of complications, and optimize referral practices accordingly to take advantage of VA care coordination and the breadth and strengths of VA’s nationwide ophthalmology program.…”
Section: Discussionmentioning
confidence: 97%
“…One case report described a Veterans Health Administration (VHA) ophthalmological asynchronous store-and-forward eye screening program in a subset of rural Georgia primary care clinics to improve access. Of those veterans screened ( n = 1443), 10.6% were homeless, almost 5% had not received an eye screening in the preceding 10 years, 10% experienced delays greater than 30 days, and 38.8% were referred for further evaluation of underlying disease [30]. In another VHA study examining the use of e-anesthesia consults ( n = 7988) across several New England medical centers (including urban and rural), low-risk surgical patients were screened for appropriateness for e-consults, which reduced patient travel and time to surgery and improved anesthesiologist efficiency [31].…”
Section: Resultsmentioning
confidence: 99%
“…Interviews with rural Iowa and Illinois veterans with HIV ( n = 13) found that specialty care telehealth access resulted in reduced median yearly travel time (150 min), time away from work, and travel costs [67]. In other VHA telemedicine studies, a remote eye screening program for rural dwelling veterans reduced the volume of necessary face-to-face visits and overall healthcare costs, saving approximately $150 per visit and $52 per patient in travel [30], and a urology program ( n = 97) reported a savings of approximately $126 in opportunity costs per appointment [68]. Similarly, in a three-year rural New England study, rheumatology patients ( n = 176) lived on average 99 miles from their rheumatologist and 22 miles from their primary care provider, with implementation of a telerheumatology program saving the health system almost $27,000 in consulting specialist travel (roughly $67 per visit) [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation